Thomas Thweatt Tredway papers - Tredway, Thomas Thweatt
ALS (1857 March 7) written by Tredway to Horace Greeley requesting Greeley's aid for a slave trying to purchase freedom; ALS (1865 February 16) written by Tredway to his daughter describing the close of the Civil War in Richmond, Va.; and notes on Tredway by Alfred J. Morrison.
Delegate to the Virginia General Assembly during the Civil War and resident of Prince Edward County, Va.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Greeley, Horace, -- 1811-1872 -- Correspondence; Morrison, Alfred J. -- 1876-1923.; Virginia. -- General Assembly; Slaves -- Virginia -- Prince Edward County; Richmond (Va.) -- History -- Civil War, 1861-1865.; United States -- History -- Civil War, 1861-1865.; Virginia -- History -- Civil War, 1861-1865.; Virginia -- Politics and government -- 1861-1865.; Legislators -- Virginia